Eudaimonia and mindfulness as predictors of alcohol-dependence: a pilot study - Allen Joshua George; Romate John; Eslavath Rajkumar; Maria Wajid; R. Lakshmi (Cogent Psychology, 2023)
AbstractBoth hedonia and eudaimonia contribute to well-being, but existing literature on alcohol-dependence concentrates on hedonic needs alone, leaving a research gap on the role of eudaimonia in alcohol-dependence. Theoretically, mindfulness promotes eudaimonia that presumably benefits individuals with alcohol-dependence, but the empirical literature on the same is scarce. Hence, the current pilot study intended to examine the association of eudaimonia and mindfulness with alcohol-dependence, and assess the feasibility of the main study. Study-I compared mindfulness and eudaimonia of individuals with (N = 154) and without (N = 160) alcohol-dependence. Its results called forth a study-II that explored the role of eudaimonia and mindfulness in predicting alcohol-dependence among the individuals undergoing treatment for alcohol-dependence (N = 110). The data were analyzed using the independent-sample t-test, Pearson correlation, and multiple linear regression. Study-I revealed the significant deficiency of mindfulness and eudaimonia among individuals with alcohol-dependence compared to those without alcohol-dependence. Study-II found that mindfulness and eudaimonia predicted alcohol-dependence and alcohol craving. Study result indicates the potential role of mindfulness and eudaimonia in the effective treatment of alcohol-dependence, through significant correlation among the variables. The study also highlights the feasibility and utility of the main study.